A Novel Fully-Human Potency-Matched Dual Cytokine-Antibody Fusion Protein Targets Carbonic Anhydrase IX in Renal Cell Carcinomas - De Luca, Roberto; Gouyou, Baptiste; Ongaro, Tiziano; Villa, Alessandra; Ziffels, Barbara; Sannino, Alessandro; Buttinoni, Gianluca; Galeazzi, Simone; Mazzacuva, Mirko; Neri, Dario (Frontiers in Oncology, 2019)
Certain cytokines synergize in activating anti-cancer immunity at the site of disease and it may be desirable to generate biopharmaceutical agents, capable of simultaneous delivery of cytokine pairs to the tumor. In this article, we have described the cloning, expression and characterization of IL2-XE114-TNFmut, a dual-cytokine biopharmaceutical featuring the sequential fusion of interleukin-2 (IL2) with the XE114 antibody in scFv format and a tumor necrosis factor mutant (TNFmut). The fusion protein recognized the cognate antigen (carbonic anhydrase IX, a marker of hypoxia and of renal cell carcinoma) with high affinity and specificity. IL2-XE114-TNFmut formed a stable non-covalent homotrimeric structure, displayed cytokine activity in in vitro tests and preferentially localized to solid tumors in vivo. The product exhibited a partial growth inhibition of murine CT26 tumors transfected for carbonic anhydrase IX. When administered to Cynomolgus monkey as intravenous injection, IL2-XE114-TNFmut showed the expected plasma concentration of ~1,500 ng/ml at early time points, indicating the absence of any in vivo trapping events, and a half-life of ~2 h. IL2-XE114-TNFmut may thus be considered as a promising biopharmaceutical for the treatment of metastatic clear-cell renal cell carcinoma, since these tumors are known to be sensitive to IL2 and to TNF.